Boolean and smoothing of discrete polygonal surfaces. (May 2016) - Updegrove, Adam; Wilson, Nathan M.; Shadden, Shawn C.
Abstract: The development of discrete solid models from imaging has become a common practice in reverse engineering. This has motivated the need for tools to combine and manipulate discrete boundary representation of objects. Despite the importance of this problem in computer aided engineering, there is a lack of robust and efficient open-source implementations of Boolean operations for discrete geometries. This paper discusses the development of new Visualization Tool Kit (VTK) classes for the Boolean and local mesh control of triangulated solid models. The implementation presented in this paper maintains the same base classes for Boolean operations in VTK version 6.2.0, but develops new procedures within these classes. Improvements are made on the robustness and performance of the Boolean algorithms for discrete surfaces. For example, for Boolean operations consisting of order 10, 000 intersecting edges, the new implementation runs an order of magnitude faster than the current Boolean implementation in VTK, and is able to handle test cases the current implementation fails to handle. In addition, surface manipulation operations were created in order to deal with issues such as surface roughness, poor quality triangles, and sharp junctions that are often encountered in discrete solid modeling. These operations are implemented locally to give increased control. A unique smoothing method is also developed to address the issue of global model distortion common to prior smoothing procedures.